Exercise as potential countermeasure for the effects of 70 days of bed rest on cognitive and sensorimotor performance - Koppelmans, Vincent; Mulavara, Ajitkumar P.; Yuan, Peng; Cassady, Kaitlin E.; Cooke, Katherine A.; Wood, Scott J.; Reuter-Lorenz, Patricia A.; De Dios, Yiri E.; Stepanyan, Vahagn; Szecsy, Darcy L.; Gadd, Nichole E.; Kofman, Igor; et al. (Frontiers in Systems Neuroscience, 2015)
BACKGROUND Spaceflight has been associated with changes in gait and balance; it is unclear whether it affects cognition. Head down tilt bed rest (HDBR) is a microgravity analog that mimics cephalad fluid shifts and body unloading. In consideration of astronaut’s health and mission success, we investigated the effects of HDBR on cognition and sensorimotor function. Furthermore, we investigated if exercise mitigates any cognitive and sensorimotor sequelae of spaceflight. METHOD We conducted a 70-day 6-degree HDBR study in 10 male subjects who were randomly assigned to a HDBR supine exercise or a HDBR control group. Cognitive measures (i.e., processing speed, manual dexterity, psychomotor speed, visual dependency, and 2D and 3D mental rotation) and sensorimotor performance (functional mobility and balance performance) were collected at 12 and 8 days pre-HDBR, at 7, 50, and 70 days in HDBR, and at 8 and 12 days post-HDBR. Exercise comprised resistance training, and continuous and high-intensity interval aerobic exercise. We also repeatedly assessed an outside-of-bed rest control group to examine metric stability. RESULTS Small practice effects were observed in the control group for some tasks; these were taken into account when analyzing effects of HDBR. No significant effects of HDBR on cognition were observed, although visual dependency during HDBR remained stable in HDBR controls whereas it decreased in HDBR exercise subjects. Furthermore, HDBR was associated with loss of functional mobility and standing balance performance, which were almost fully recovered 12 days post-HDBR. Aerobic and resistance exercise partially mitigated the effects of HDBR on functional mobility and accelerated the recovery time course post-HDBR. DISCUSSION HDBR did not significantly affect cognitive performance but did adversely affect functional mobility and standing balance performance. Exercise had some protective effects on the deterioration and recovery of functional mobility.